INTEGRASI EKOLITERASI DALAM PEMBELAJARAN BAHASA INDONESIA DI SMP NEGERI 1 PEJAWARAN UNTUK MENDUKUNG SDGS - Prasanty, Arum Berliana; Suroso, Eko (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
This study aims to describe and analyze the integration of ecoliteracy values in Indonesian language learning at SMP Negeri 1 Pejawaran, as well as their connection with SDG 4 (Quality Education) and SDG 13 (Climate Action). The study employs a descriptive qualitative approach with subjects including Indonesian language teachers, students from grades VII–IX, and school administrators. Data were collected through observation, interviews, and document analysis, then analyzed through reduction, presentation, and conclusion drawing. The results indicate that the integration of ecoliteracy encompasses three domains: (1) Cognitive, in the form of understanding ecological concepts through environment-themed texts; (2) Affective, through the enhancement of empathy and ecological responsibility; and (3) Psychomotor, through tangible actions such as literacy projects and sustainability campaigns. The learning strategies include Contextual Teaching and Learning (CTL), Project Based Learning (PjBL), and the reflective collaborative approach integrated into the co-curricular project with the theme of Sustainable Lifestyles. This integration has been proven to enhance writing skills, ecological awareness, and student participation in environmental actions. Indonesian language learning based on ecoliteracy effectively fosters students' ecological literacy and supports the implementation of sustainable education in schools. ABSTRAKPenelitian ini bertujuan mendeskripsikan dan menganalisis integrasi nilai-nilai ekoliterasi dalam pembelajaran Bahasa Indonesia di SMP Negeri 1 Pejawaran, serta keterkaitannya dengan SDG 4 (Pendidikan Berkualitas) dan SDG 13 (Penanganan Perubahan Iklim). Penelitian menggunakan pendekatan kualitatif deskriptif dengan subjek guru Bahasa Indonesia, siswa kelas VII–IX, dan pihak sekolah. Data dikumpulkan melalui observasi, wawancara, dan analisis dokumen, kemudian dianalisis dengan reduksi, penyajian, dan penarikan kesimpulan. Hasil menunjukkan bahwa integrasi ekoliterasi mencakup tiga ranah: (1) Kognitif, berupa pemahaman konsep ekologis melalui teks bertema lingkungan; (2) Afektif, melalui penguatan empati dan tanggung jawab ekologis; dan (3) Psikomotor, melalui aksi nyata seperti proyek literasi dan kampanye keberlanjutan. Strategi pembelajaran meliputi Contextual Teaching and Learning (CTL), Project Based Learning (PjBL), dan pendekatan kolaboratif reflektif yang terintegrasi dalam proyek kokurikuler bertema Gaya Hidup Berkelanjutan. Integrasi ini terbukti meningkatkan kemampuan menulis, kesadaran ekologis, dan partisipasi siswa dalam aksi lingkungan. Pembelajaran Bahasa Indonesia berbasis ekoliterasi efektif menumbuhkan literasi ekologis siswa dan mendukung implementasi pendidikan berkelanjutan di sekolah.